Letter - Rathbone, Eleanor F. (Eleanor Florence), 1872-1946
038-0045-001 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMAN: THE EARL OF LISTOWEL MISS ELEANOR RATHBONE, M.P. HON. SECRETARIES: Mr. D.R. GRENFELL, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. WILFRID ROBERTS, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. ASSISTANT SECRETARY: FELICE CLARK. 30, ECCLESTON STREET, LONDON, S.W.1. TELEPHONE: SLOANE 9866 50, ROMNEY STREET, WESTMINSTER. S.W.1. 8th April, 1940. Dear Mr Tewson, The Duchess asked me to read the enclosed letter to you before posting it, as she does not feel quite up-to-date about the situation. It is true that we have already had some stiff claims for dilapidations and that we are financially in a bad way. But my own feeling is that it would be just as well if your Committee could defer a decision as to what further funds they would be good enough to allow us until the position is rather clearer. We may possibly get a grant from the Government on a 50/50 basis or something of that sort, and in that case it would be as well to have some prospect of further grants from voluntary sources on which we could claim Government money. We will try to fix up a meeting of the Basque Children's Committee as soon as possible, after consulting you as to date. Yours sincerely, Eleanor F. Rathbone H.V. Tewson, Esq., Trades Union Congress, Transport House, S.W.1. 292/946/38/45